1984
DOI: 10.1021/np50036a009
|View full text |Cite
|
Sign up to set email alerts
|

Components of Oil of Tansy (Tanacetum vulgare) That Repel Colorado Potato Beetles (Leptinotarsa decemlineata)

Abstract: The steam distillate of fresh leaves and flowers of tansy, Tanucetum vulgare, was found to be strongly repellent to Colorado potato beetles, Lptinorursa daemlineuta. Liquid chromatography detected 56 compounds present. Identification of compounds was by gc/ms. The major components, camphor (30%) and umbellulone (25%), show the plant to be a previously unreported chemotype. A commercial oil of tansy was also found to be highly repellent to Colorado potato beetles; gclms analysis found bornyl acetate (74%) to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 4 publications
2
28
0
1
Order By: Relevance
“…Especially Tanacetum parthenium (L.) Schultz Bip (feverfew) is a known remedy for the treatment of various diseases, including arthritis, fever, vertigo, migraine, menstrual disorders, stomach-ache, toothache, insect bites and psoriasis (Ernst and Pittler, 2000). According to recent studies, essential oils and extracts of Tanacetum genus exhibit anti-inflammatory (Brown et al, 1997;Ghantous et al, 2013;Mordujovich-Buschiazzo et al, 1996;Park et al, 2011;Sur et al, 2009), anticancer (Ghantous et al, 2013), antibacterial (Habibi et al, 2009;Hethelyi et al, 1991;Holopainen and Kauppinen, 1989;Mohsenzadeh et al, 2011), antiviral (Onozato et al, 2009), antifungal (Hethelyi et al, 1991), antihelmintic (Godinho et al, 2014), insecticidal (Hough-Golstein and Hahn, 1992;Nottingham et al, 1991;Panasiuk, 1984;Schearer, 1984;Suomi et al, 1986) and antiprotozoal effects (Izumi et al, 2008;Tiuman et al, 2005). Many studies have been reported on the essential oil composition of various Tanacetum species (El-Shazly et al, 2002;Goren et al, 2001;Greche et al, 2000;Judzentiene and Mockute, 2005;Kandemir et al, 2008;MajedJabari et al, 2002;Marongiu et al, 2009;Mockute and Judzentiene, 2004;Monfared et al, 2002;Piras et al, 2014;Polatoglu et al, 2011;Rohloff et al, 2004;Weyerstahl et al, 1999) and camphor, 1,8-cineole, ␣-thujone, carv...…”
Section: Introductionmentioning
confidence: 99%
“…Especially Tanacetum parthenium (L.) Schultz Bip (feverfew) is a known remedy for the treatment of various diseases, including arthritis, fever, vertigo, migraine, menstrual disorders, stomach-ache, toothache, insect bites and psoriasis (Ernst and Pittler, 2000). According to recent studies, essential oils and extracts of Tanacetum genus exhibit anti-inflammatory (Brown et al, 1997;Ghantous et al, 2013;Mordujovich-Buschiazzo et al, 1996;Park et al, 2011;Sur et al, 2009), anticancer (Ghantous et al, 2013), antibacterial (Habibi et al, 2009;Hethelyi et al, 1991;Holopainen and Kauppinen, 1989;Mohsenzadeh et al, 2011), antiviral (Onozato et al, 2009), antifungal (Hethelyi et al, 1991), antihelmintic (Godinho et al, 2014), insecticidal (Hough-Golstein and Hahn, 1992;Nottingham et al, 1991;Panasiuk, 1984;Schearer, 1984;Suomi et al, 1986) and antiprotozoal effects (Izumi et al, 2008;Tiuman et al, 2005). Many studies have been reported on the essential oil composition of various Tanacetum species (El-Shazly et al, 2002;Goren et al, 2001;Greche et al, 2000;Judzentiene and Mockute, 2005;Kandemir et al, 2008;MajedJabari et al, 2002;Marongiu et al, 2009;Mockute and Judzentiene, 2004;Monfared et al, 2002;Piras et al, 2014;Polatoglu et al, 2011;Rohloff et al, 2004;Weyerstahl et al, 1999) and camphor, 1,8-cineole, ␣-thujone, carv...…”
Section: Introductionmentioning
confidence: 99%
“…that feed upon tansy towards the ant Myrmica rubra, a generalist predator. Tansy (Chrysanthemum vulgare, Asteraceae) is well known to contain numerous bioactive components, among them insect repellents (Panasiuk 1984;Schearer 1984;Teuscher and Lindequist 1994) which might be discharged by tansy-feeding herbivores with their faeces for defensive purposes. Several herbivorous insects protect themselves by sequestering compounds of the food plant, which have a feeding deterrent or repellent eect on predators (Duey 1980;Pasteels et al 1988b;Harborne 1993;Dettner et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Repellent effects of different plant extracts against insect pest species has been tested in many studies with some promising results (Schearer, 1984;Wyrostkiewicz, 1987;Chiasson et al, 1994;Mateeva, 1998;Przybylski, 2002;Pavela, 2004;Sarbu et al, 2004;Wawrzyniak & Lamparski, 2008). Among the plant extracts tested, the greatest repellency was observed with A. millefolium extract with 0.01% proportional repellency in the first 15 min.…”
Section: Resultsmentioning
confidence: 99%